Scalable Electrospinning Methods to Produce High Basis Weight and Uniform Drug Eluting Fibrous Biomaterials - Hernandez, Jamie L.; Doan, My-Anh; Stoddard, Ryan; VanBenschoten, Hannah M.; Chien, Shin-Tian; Suydam, Ian T.; Woodrow, Kim A. (Frontiers in Biomaterials Science, 2022)
Electrospinning is a process for fabricating nonwoven fibrous materials of versatile composition and form that has shown enormous promise as medical wound dressings, tissue engineered scaffolds, and for pharmaceutical delivery. However, pharmaceutical application and clinical translation of electrospun fibers requires a scalable process to control mass deposition and uniformity in the finished materials. Here, we show that free-surface electrospinning using a stationary wire electrode can generate fiber materials with high productivity and controllable deposition to achieve uniform area density (basis weight) that is relevant for scalable pharmaceutical dosage form production. Using a production-scale instrument, we performed statistically designed optimization experiments to identify a combination of parameters that improved productivity up to 13 g/hr. By combining this optimization with process controls for dynamic movement of the electrospinning substrate, we also demonstrate the production of uniform and high area density materials of 50-120 gram per square meter. We verified our process by fabricating a triple drug solid dosage form at a high area target density (100 g/m2) that largely showed less than a 10% coefficient of variation in mass or drug content. The process developed here provides a general approach for optimizing different material compositions for high productivity and uniformity, and advances the use of free-surface electrospinning for manufacturing fiber-based biomedical materials.